Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.stemcr.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

GATA6-AS1 Regulates GATA6 Expression to Modulate Human Endoderm Differentiation

Abstract: Summary Transcriptome analysis has uncovered a series of long noncoding RNAs (lncRNAs) transcribed during cell differentiation, but how lncRNA is integrated with known transcriptional regulatory network is poorly understood. Here, we utilize human definitive endoderm differentiation as a model system and decipher the functional interaction between lncRNA and key transcriptional factor. We have identified GATA6-AS1 , an lncRNA divergently transcribed from the GATA6 locus, is hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…CHIR99021 (CHIR), also known as GSK3 inhibitor, could induce GATA6 expression for hepatic differentiation from human embryonic stem cells [ 37 ]. Also, down-regulated GSK3 could induce upregulation of GATA6 in cancer cells [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…CHIR99021 (CHIR), also known as GSK3 inhibitor, could induce GATA6 expression for hepatic differentiation from human embryonic stem cells [ 37 ]. Also, down-regulated GSK3 could induce upregulation of GATA6 in cancer cells [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mRNA expression analysis indicated that both knockout and wild-type EBs highly expressed lineage markers, while the pluripotent markers were downregulated compared to undifferentiated ESCs ( Figure 5D ). We further performed directed definitive endoderm differentiation assay ( Figure 5E ; Yang et al, 2020 ). After 3 days of treatment with Activin A, KDM6-knockout ESCs could be induced to FOXA2-positive and OCT-negative endoderm cells by immunofluorescence examination ( Figure 5F ); flow cytometric analysis based on endoderm markers CXCR4 and SOX17 indicated that KDM6-knockout ESCs kept the endoderm differentiation capacity, although much lower than wild-type ESCs ( Figure 5G ), which was consistent with a previous study ( Jiang et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…For definitive endoderm differentiation, the endoderm differentiation medium [50% IMDM and 50% F12, supplemented with 0.5% B27 without vitamin A, 0.2% BSA (YEASEN, #B57370), and 100 ng/ml activin A (PeproTech, # 120-14P)] was applied for 3 days ( Yang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…To further investigate the functional role of CHD8 in lineage determination of human ESCs, we first performed the definitive endoderm differentiation [ 34 ]. After differentiation, we analyzed the expression levels of endoderm markers ( FOXA2, SOX17 , and GATA6 ) and pluripotent markers ( OCT4 and SOX2 ) by RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%